Enunciação estético-marginal no discurso literário Contos negreiros, de Marcelino Freire - Matos, Edmar Ferreira de (2021)
This Dissertation is located in the line of research Texto e discurso nas modalidades oral e escrita and has the aesthetic-marginal enunciation as its theme. Considering the discourse as a verbal activity in context, the aesthetic-marginal enunciation confers a social dimension bringing discursive marks that translate, through the scenography, the space where it is conceived and through which the ills of the marginalized people are denounced. In this way, the research is justified by the fact that writers from the periphery stand out with productions that echo the various faces of social differences. The problem starts from this question: How does Freire's literary discourse operationalize the scenography, the discursive ethos, the linguistic code and the interdiscourse to produce artistic, political and cultural effects in three texts in the work Contos negreiros? The general objective is to understand the artistic, political and cultural aspects of Freire's literary discourse and we have outlined as specific objectives: 1) to verify the constitution of the scenography, the discursive ethos and the paratopia and 2) to identify the linguistic marks that characterize the marginal literary discourse. The theoretical contribution of this research, of qualitative-bibliographic character, is constituted by the studies in the field of Discourse Analysis of French line in the enunciative-discursive perspective of Maingueneau (1997, 1998, 2005, 2008, 2010, 2013, 2015, 2016, 2018) and as for the studies of literary marginality we use the contributions of Gonzaga (1981), Ponge (1981), Hollanda (2004), Ferréz (2005), Vasconcelos (2007), Schollhammer (2009), Patrocínio (2013), and Vieira (2015 ). The corpus consists of three short stories, taken as discourse, from the book Contos Negreiros, by Marcelino Freire. We chose as categories of analysis: the scenography, the discursive ethos, the language code, the interdiscourse and the paratopia, condition of the literary discourse. The result indicates that Freire's literary discourse reflects on the militancy of an enunciator marginalized by the given mode, above all, investment in language code and mobilization of scenography